English Graduate Students’ Motivation in the Emergency Remote Learning amidst Pandemic in a Public University in Indonesia - Irfiana, Khusna (Master Program in Linguistics, Diponegoro University, 2023)
Keeping students motivated is the key to adding to the quality of the process and learning outcomes. However, due to the coronavirus outbreak disruption, students have to move to temporary remote instruction. Moving through a changing time has significantly influenced the motivation of students. The research investigated the students' motivation towards remote learning and the factors that influenced their motivation. The investigation method was qualitative descriptive using questionnaires involving 38 English graduate students at one of the public universities in Indonesia. Interviews and document analysis were carried out to further explore the participants' answers to the questionnaire. The findings showed that regardless of the pandemic disruption, the student's learning motivation was relatively high, as indicated by students' willingness to learn, students' beliefs about learning outcomes, students' participation in online learning, and student's performance on course assignments. Various factors, such as the environment, the school system, and social life, have also influenced their education. The lack of interaction between teacher and student has affected their understanding during the learning process. Hence, the study recommends institutions' involvement in a cooperative learning program that can assist students in need of additional support and reinforce their English learning motivation during emergency remote learning.